Highway Network Expansion in Andean Patagonia: a Warning Notice From Rufous-legged Owls - Ojeda, Valeria Susana (2015)
As part of the economic and population growth of Patagonia, several dust/gravel roads crossing well preserved Andean forests are being converted into paved highways. The potential effects of these changes on forest wildlife have been little studied. The Rufous-legged Owl (Strix rufipes) was dominant among road-killed birds in our survey of a 27-km section of highway running through forests of Nahuel Huapi National Park, in Argentine Patagonia. Fatalities were not evenly distributed along the surveyed length of the road, so we investigated whether landscape features, roadside slope on both sides of the highway, demography, and/or season explained the aggregation pattern. Patterns of distribution of the road-killed owls were explained by owl abundance and age-class, time of year, and hour, and were weakly related to canopy closure; roadside slope on both sides was unrelated to abundance of fatalities. Trafficrelated deaths were likely the primary cause of non-natural mortality of Rufous-legged Owls (especially for young individuals) in the study area. Examination of carcasses indicated that most owls were killed by turbulence behind large vehicles and that deaths occurred early in the night. Semi-trailer trucks capable of carrying large loads, which peak in numbers between dusk and midnight, likely caused most  fatalities. A wayto reduce owl mortality could be to schedule truck traffic outside the hours when owls are most active at hunting around paved roads crossing natural forests, at least during late winter and spring seasons. Because transportation networks encourage future development that will affect the environment in a variety of ways, it is critical to retain roadless and near-roadless (i.e., having only dirt or gravel roads with slow-moving traffic) portions of the southern Andes to preserve their natural landscapes.